(untitled) (Indian Journal of Animal Production and Management, 2024)
Animal behaviour comprises all the ways and manners in which animals relate with members of their species, animals of other species and their environment. India has a large population of livestock and umpteen breeds inhabiting in diverse agro-ecological regions. The behavioural repertoire of these breeds and distinguishing features of behaviour among different breeds has sparsely been explored. Knowledge of animal behaviour is a pivotal area of animal production and welfare, yet most neglected by researchers, developmental departments and farmers in India either due to ignorance or neglect. Behaviour is generally the animal’s “first line of defence” in response to environmental change. Careful observations of behaviour can provide with a great deal of information about animals’ requirements, preferences and dislikes and internal states. An in depth knowledge of behaviours of farm animals, therefore, is indispensable to their handling, productivity, welfare and profitability. This paper attempts to address the importance of studying the behaviour especially of indigenous breeds of livestock, which is sine qua non to their handling and management.